Perceptions of intermediate teachers and librarians regarding the school library programs of the public elementary schools in district IB, Division of City Schools, Manila - Sianghio, Myrna L.; Hidalgo, Namnama P.; Buenrostro, Juan Jr. C. (Quezon City Institute of Library Science, University of the Philippines Diliman, 1987)
The study aims to determine the strengths and weaknesses of the school library program in the eleven public elementary schools of District IB in the Division of City Schools, Manila as perceived by 280 intermediate classroom teachers (142 Grade Five and 138 Grade Six) in five subjects (eighty-four teachers of English, fifty-one Mathematics teachers, fifty-six Pilipino teachers, forty-four Science teachers and forty-five Social Studies teachers) and twenty-seven librarians in terms of seven aspects of the school library programs namely: 1) program objectives; 2) library staff; 3) library resources; 4) library quarters; 5) library organization and administration; 6) library utilization; and 7) library services. These perceptions were compared by groups as follows: Grade Five and Grade Six teachers; teachers handling the different subjects; and teachers and librarians.
The data gathering instrument was a questionnaire checklist. The questionnaire is a modified version of the New York State Education Department Cooperative Review Service Self-Study Guide for the School Library. It consists of various statements about specific features of seven aspects of the school library program. The respondents were required to indicate whether the specific feature is a strong aspect of the school library program or whether improvements are needed in that aspect.
To test the hypotheses, t-test and analysis of variance (ANOVA) were used. The t-test was utilized to compare the weighted means of the perceptions of two groups such as teachers and librarians and Grade Five and Grade Six teachers. ANOVA was used to test the significance of differences between the means of the perceptions of teachers handling the different subjects.
In general, the school library programs is perceived to be moderately strong by the teachers and librarians. School library program objectives were perceived as the strongest aspect (very strong) followed by library services, library staff, library organization and administration, library utilization, and library quarters, in that order, which were all perceived to be moderately strong aspects. Only the library resources were perceived to need some improvement.
The statistical tests showed that the different groups had similar perceptions of the different aspects. The differences in the weightd means of their perceptions were shown to be statistically not siginificant.
Mimeographed.
Special Problem (Master of Library Science)
Keywords: School libraries -- Philippines -- Manila; School libraries -- Evaluation. -- Philippines -- Manila